VIKTIMISASI PEREMPUAN MELALUI BODY SHAMING - Fauziah, Dwi Putri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This article discusses bullying, especially body shaming that occurs in women. Body shaming is a form of negative commentary about a person's body, but the main problem for the author is the act of body shaming that often occurs only to women. The author will discuss the victims of women, where those who experience body shaming are inseparable from patriarchal culture, where the culture considers that women are helpless creatures. In the act of body shaming media also plays a role in forming the ideal standard of a woman's body, which causes women to be more vulnerable in becoming victims of body shaming.